ILC3, a Central Innate Immune Component of the Gut-Brain Axis in Multiple Sclerosis - Miljković, Đorđe; Jevtić, Bojan; Stojanović, Ivana; Dimitrijević, Mirjana (Frontiers in Immunology, 2021)
Gut immune cells have been increasingly appreciated as important players in the central nervous system (CNS) autoimmunity in animal models of multiple sclerosis (MS). Among the gut immune cells, innate lymphoid cell type 3 (ILC3) is of special interest in MS research, as they represent the innate cell counterpart of the major pathogenic cell population in MS, i.e. T helper (Th)17 cells. Importantly, these cells have been shown to stimulate regulatory T cells (Treg) and to counteract pathogenic Th17 cells in animal models of autoimmune diseases. Besides, they are also well known for their ability to stabilize the intestinal barrier and to shape the immune response to the gut microbiota. Thus, proper maintenance of the intestinal barrier and the establishment of the regulatory milieu in the gut performed by ILC3 may prevent activation of CNS antigen-specific Th17 cells by the molecular mimicry. Recent findings on the role of ILC3 in the gut-CNS axis and their relevance for MS pathogenesis will be discussed in this paper. Possibilities of ILC3 functional modulation for the benefit of MS patients will be addressed, as well.